ON IMPROVEMENT OF METHOD OF CALCULATION OF TRACTION FORCE OF AIT - Yaroshenko, P.N. (Bulletin of Sumy National Agrarian University. The series: Mechanization and Automation of Production Processes, 2021)
The article considers the issue of improving the method of calculating the rational composition of the machine-tractor unit. Studies on the dependences for determining the traction force of modern tractors have shown that a number of researchers addressed this problem long before its occurrence. In the technical literature for modern tractors there is less and less information on performance. Basically, this is advertising information, but even on its basis you can determine the necessary parameters. As can be seen from this publication, the traction force must be determined at least twice, taking into account the operating conditions of the units. It is necessary to know the weight of the units, the value of their technological speeds and what transmission this unit uses. This is especially important when the AIT consists of a foreign tractor and a domestic agricultural machine, because the capabilities of energy products of well-known brands have a significant range, and the capabilities of domestic equipment are limited by agronomic requirements.